Development and validation of the Meiji Nutritional Profiling System for children - Wakayama, Ryota; Yu, Tao; Drewnowski, Adam; Takasugi, Satoshi; Horimoto, Tomohito; Tsutsumi, Chiharu (Frontiers in Nutrition, 2025)
BackgroundThe Meiji Nutritional Profiling System (Meiji NPS) takes into account life-stage differences and addresses specific health challenges in different age groups in Japan.ObjectivesThis study aimed to develop the Meiji NPS for younger (3–5 years) and older (6–11 years) children to encourage product reformulation and promote proper growth and development.MethodsMeiji NPS scores for 1,091 foods listed in the Japanese Food Standard Composition Table were calculated and compared with nutrient profiles (NPs) for children developed by the WHO Regional Office for the Western Pacific or Nutrient-Rich Foods Index 9.3 (NRF9.3).ResultsFor younger children, the Meiji NPS scores ranged from −442.3 to 423.9, and for older children, the Meiji NPS scores ranged from −265.5 to 386.5. The Meiji NPS scores showed significant differences (p < 0.001) between healthy and unhealthy foods, when classified according to the WHO NP model. There was also a strong correlation between the Meiji NPS and NRF9.3, validating the new NPS system (r = 0.73).ConclusionThe Meiji NPS for younger and older children may provide a useful incentive for Japanese food manufacturers to produce healthier products.